2004
DOI: 10.1093/jnci/djh002
|View full text |Cite
|
Sign up to set email alerts
|

Active Smoking, Household Passive Smoking, and Breast Cancer: Evidence From the California Teachers Study

Abstract: Our study provides evidence that active smoking may play a role in breast cancer etiology and suggests that further research into the connection is warranted, especially with respect to genetic susceptibilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
209
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(242 citation statements)
references
References 57 publications
24
209
1
8
Order By: Relevance
“…If smoking prior to first birth is strongly associated with survival, then we may have missed an important association. However, two prospective studies of incident cases only did not find an association (Egan et al, 2002;Reynolds et al, 2004), and when we restricted our analyses to incident cases only, although imprecise there was no evidence of an association. Breast cancer cases were not confirmed histologically and selfreported breast cancer may be inaccurate.…”
Section: Study Limitationsmentioning
confidence: 79%
See 1 more Smart Citation
“…If smoking prior to first birth is strongly associated with survival, then we may have missed an important association. However, two prospective studies of incident cases only did not find an association (Egan et al, 2002;Reynolds et al, 2004), and when we restricted our analyses to incident cases only, although imprecise there was no evidence of an association. Breast cancer cases were not confirmed histologically and selfreported breast cancer may be inaccurate.…”
Section: Study Limitationsmentioning
confidence: 79%
“…(Adami et al, 1988;Hunter et al, 1997;Lash and Aschengrau, 1999;Innes and Byers, 2001;Egan et al, 2002;Band et al, 2002;Lash and Aschengrau, 2002;Kropp and Chang-Claude, 2002;Fink and Lash, 2003;Reynolds et al, 2004) The pooled analysis for these 11 studies, together with the study presented here, included 6528 breast cancer cases and provided an odds ratio (95% CI) of 1.07 (0.94, 1.22) (Figure 1). The pooled estimates from differing sensitivity analyses to assess the effect of different exposure measures did not differ substantively from this estimate (all odds ratios for these analyses were between 1.05 and 1.08).…”
Section: Meta-analysismentioning
confidence: 96%
“…2000; Kropp and Chang-Claude, 2002) and others showed no effect (Wartenberg et al, 2000;Nishino et al, 2001;Egan et al, 2002;Lash and Aschengrau, 2002;Gammon et al, 2004;Reynolds et al, 2004;Shrubsole et al, 2004;Bonner et al, 2005;Hanaoka et al, 2005;Lissowska et al, 2006). Recent reviews of the literature have also been inconsistent with two showing that there was an association between passive smoking and breast cancer (Johnson, 2005;Miller et al, 2007) and a further two suggesting that more evidence is needed before any conclusions can be drawn (IARC, 2004;US Surgeon General, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, only about half of the published studies provided results stratified by menopausal status (Wells, 1991;Millikan et al, 1998;Delfino et al, 2000;Johnson et al, 2000;Gammon et al, 2004;Reynolds et al, 2004;Shrubsole et al, 2004;Bonner et al, 2005;Hanaoka et al, 2005;Lissowska et al, 2006) and therefore the possibility of publication bias cannot be ruled out. The current study adds to the totality of the evidence suggesting that exposure to passive smoking in the home is not associated with an increase in the risk of breast cancer, and does not support the view that there is an increased risk in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports suggesting that cigarette smoking has little or no independent effect on breast cancer risk (Baron, 1984;London et al, 1989;Baron et al, 1996). Furthermore, a meta analysis of 53 epidemiological studies suggested a little or no independent effect of smoking on the risk of developing breast cancer (Hamajima et al, 2002), but the recent California Teachers Study has provided evidence that active, but not passive smoking increases breast cancer risk (Reynolds et al, 2004).…”
Section: Introductionmentioning
confidence: 99%